Upper Quadrant Edema Patient-Reported Outcome Measure Is Reliable, Valid, and Efficient for Patients With Lymphatic and Venous Disorders. Issue 12 (27th September 2021) - Deutscher, Daniel; Hayes, Deanna; Cook, Karon F; Werneke, Mark W; Tucker, Carole A; Mioduski, Jerome E; Levenhagen, Kim; Tidhar, Dorit; Pfarr, Megan; Kallen, Michael A
Abstract: Objective: The main aims of this study were to (1) create a patient-reported outcome measure (PROM) item bank for measuring the impact of upper quadrant edema (UQE) on physical function by calibrating responses to newly developed items; and (2) assess reliability, validity, and administration efficiency of scores based on computerized adaptive test (CAT) and 10-item short-form (SF) administration modes. Methods: This was a retrospective study including data from patients treated in outpatient rehabilitation clinics for UQE that responded to all 27 candidate items at intake. Item response theory model assumptions of unidimensionality, local item independence, item fit, and presence of differential item functioning were evaluated. UQE-CAT– and UQE-SF–generated scores were assessed for reliability, validity, and administration efficiency. Results: The total cohort included 3486 patients (mean [SD] age = 61 [13] years; range = 14–89 years). After removing 2 items, a 25-item solution was supported for its unidimensionality and fit to the item response theory model with reliability estimates of more than 0.93 for scores based on both CAT and SF administration modes. No items demonstrated differential item functioning. Scores discriminated among multiple patient groups in clinically logical ways and were moderately responsive to change with negligible floor and acceptable ceiling effects. CAT scores were generated using an average of 5.6 items (median = 5). Conclusion: Scores on the UQE PROM were reliable, valid, and efficient for assessing perceived physical function of patients with upper quadrant edema; thus, the measure is suitable for research and routine clinical administration. Impact: The newly developed UQE PROM is reliable and valid and offers efficient administration modes for assessing perceived physical function of patients with UQE caused by lymphatic and venous disorders, both for research and routine clinical care in busy outpatient rehabilitation settings. As an item response theory–based measure, the UQE PROM allows administration of condition-specific functional questions with low response burden for patients. This study supports a transition to PROMs that are based on modern measurement approaches to achieve high accuracy and efficiency.